2007
DOI: 10.1002/ibd.20041
|View full text |Cite
|
Sign up to set email alerts
|

How Adherent to Treatment With Azathioprine Are Patients With Crohnʼs Disease in Long-term Remission?

Abstract: Most patients with Crohn's disease in longstanding remission had low self-reported adherence to azathioprine. Both male gender and single status were associated with nonadherence to azathioprine, whereas disease factors were not related to self-reported adherence. Patients considered nonadherent to treatment maintained disease remission and a quality of life similar to patients who were adherent to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 27 publications
2
27
4
2
Order By: Relevance
“…Similarly, in the study of Shale and Riley [21] , in addition to being young, having education beyond the age of 16 years and being in full-time employment, being prescribed a 3-times-a-day regimen was identified as predictor for non-adherence. The need to take medicine during working hours (P = 0.001, OR: 3.5, 95% CI: 2.27-5.26), and multiple daily doses (P = 0.045, OR: 2.8, 95% CI: 0.99-7.70) were significantly associated with non-adherence in adults [22] , which was also confirmed by other studies [20,21] . Similarly, adolescents whose regimen involved more than one daily medication administration had more adherence barriers [26] .…”
Section: Drug Type and Dosing Regimessupporting
confidence: 82%
See 2 more Smart Citations
“…Similarly, in the study of Shale and Riley [21] , in addition to being young, having education beyond the age of 16 years and being in full-time employment, being prescribed a 3-times-a-day regimen was identified as predictor for non-adherence. The need to take medicine during working hours (P = 0.001, OR: 3.5, 95% CI: 2.27-5.26), and multiple daily doses (P = 0.045, OR: 2.8, 95% CI: 0.99-7.70) were significantly associated with non-adherence in adults [22] , which was also confirmed by other studies [20,21] . Similarly, adolescents whose regimen involved more than one daily medication administration had more adherence barriers [26] .…”
Section: Drug Type and Dosing Regimessupporting
confidence: 82%
“…In contrast, other studies reported low adherence rates after long-term remission [3,22] . Very high non-adherence rates (74.3%) were reported for azathioprine in CD patients who were in long-term (> 48 mo) clinical remission [20] . Moreover, a direct association between adherence and risk of relapse was reported in UC.…”
Section: Age and Disease Durationmentioning
confidence: 98%
See 1 more Smart Citation
“…19,20 In inflammatory bowel disease adherence to treatment seems to be correlated with disease activity. [21][22][23] Kane et al 23 have shown that nonadherence to medication was up to 60% in patients with quiescent UC, while adherence to thiopurine was more than 90% in out-patients with active CD. 20 Mantzaris et al 22 found that most patients with CD in long-standing remission had self-reported low adherence to treatment.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4] It has proven particularly useful in the treatment of inflammatory bowel disease (IBD). [5][6][7][8][9][10] The effect of azathioprine is at least partially due to triggering of lymphocyte apoptosis. [11][12][13][14] Side effects of azathioprine include anemia, which has been attributed to hemophagocytic syndrome and bone marrow suppression.…”
mentioning
confidence: 99%